Rethinking the City Symphony after the Age of Industry : Harun Farocki and the ‘City Film’ - Cowan, Michael (Intermédialités / Intermediality, 2008)
Abstract Harun Farocki’s films and installation works have often revisited the question—central to the history of experimental filmmaking—of the city and its representability. Focusing on Farocki’s recent installation Gegen-Musik, this article explores his efforts to reconfigure the genre of the Stadtsinfonie (city symphony) for a post-industrial era. To the difference of other recent efforts to renew modernist strategies for representing the city, Farocki interrogates the possibility of such a genre in an era characterized by the marginalization of human labor, industry and the image itself.